Electrospinning of cyanoacrylate tissue adhesives for human dural repair in endonasal surgery. Issue 3 (1st October 2021) - Campbell, Brooke; Anderson, Zoe; Han, Daewoo; Nebor, Ivanna; Forbes, Jonathan; Steckl, Andrew J.
Abstract: Cerebral spinal fluid (CSF) leakage is a major postoperative complication requiring surgical intervention, resulting in prolonged healing and higher costs. Biocompatible polymers, such as cyanoacrylates, are currently used as tissue adhesives for closing surgical defects and incisions. Coupling these polymers with nanofiber technology shows promising results for generating nanofibers used in wound care, tissue engineering, and drug delivery. Fiber membranes formed by electrospinning of n‐ octyl‐2‐cyanoacrylate (NOCA) are investigated for in situ dural closures after neurosurgery to improve the quality of the closure and prevent post‐surgical CSF leaks. Electrospun NOCA fiber membranes showed significantly higher sealing capabilities of defects in human dura, with an average burst pressure of 149 mmHg, compared with that of an FDA‐approved common dural sealant that had an average burst pressure of 37 mmHg. In this study, microfabrication of NOCA fibers demonstrates a promising technique for dural repairs.